223 A Novel Immunoglobulin G Autoantibody Against Low Density Lipoprotein (LDL) with Pathogenic Functions. (31st May 2014) - Khamis, Ramzi; Woollard, Kevin; Boyle, Joseph; Chang, Shang-Hung; Hyde, Gareth; Johns, Michael; Haskard, Dorian
Abstract : Introduction: IgG autoantibodies reacting with different forms of modified LDL are found in blood and have been associated with cardiovascular events related to atherosclerosis. However there is a controversy as to whether such antibodies are pathogenic. We set out to generate monoclonal autoantibodies reacting with LDL for further mechanistic studies. Methods/Results: We fused splenocytes from a LDL receptor deficient ( Ldlr -/- ) atherosclerotic mouse with the Sp2/0 myeloma cell line, and screened hybridoma culture supernatants by ELISA for reactivity with solid-phase LDL. We selected a monoclonal IgG2b antibody, designated LO9. Sequencing of the LO9 variable heavy (VH ) and variable light (VL ) regions revealed numerous somatic mutations in the complementarity determining regions (CDR) of both the VH and VL . Together with the IgG2b subclass, these indicate that LO9 is not a natural antibody but has developed from an adaptive immune response. To investigate interaction of LO9 with LDL we performed in vitro binding assays. LO9 reacted with LDL directly adherent to ELISA plates, but not with LDL immobilised by polyclonal anti-apoB. Less reactivity was noted with Cu ++ oxidised-LDL and malondialdehyde-conjugated LDL (MDA-LDL). LO9 binding to adherent LDL was not inhibited by fluid-phase LDL in excess and the LO9 epitope was not abolished by organic solvents, suggesting that it is not lipid. In functional assays, addition of macrophages to LO9 bound to adherent LDL in vitro led to significant TNF release, an effect that was blocked by inhibition of Fc gamma receptors (FcγRs), and which was not seen when macrophages were incubated with adherent LDL alone. Expression of the LO9 epitope on adherent LDL was greatly increased by incubation with conditioned medium (CM) from activated macrophages, consistent with the LDL epitope being further revealed by the action of macrophage-derived factors. Expression of the LO9 epitope in atherosclerosis was confirmed by immunohistochemical staining of human and mouse lesions. Following intra-venous injection of LO9 labelled with a near infra-red dye (LO9–750), fluorescence molecular tomography imaging demonstrated specific localisation to a region of interest covering the aortic arch of Ldlr -/- mice but not wild type animals. Confocal microscopy of extracted aortae en face confirmed that LO9 localised in atherosclerotic regions beneath endothelium and in the vicinity of macrophages. Conclusions: We believe LO9 is the first example of an autoantibody that reacts with an allosteric epitope on LDL, revealed by adhesion to a surface and/or by the action of factors derived from activated macrophages. Binding of LO9-like antibodies to LDL trapped on matrix in the arterial wall could lead to promotion of atherosclerosis via ligation of macrophage FcgRs and release of TNF and other proinflammatory mediators.